Manuscripts and islamic historical studies in Indonesia - H. Uka Candrasasmita (Center for Research and Development of Religious Literature and Heritage Agency for Research & Development, and Training Departement and Religious Affairs of the Republic of Indonesia, 2016)
shd,1/ws.c.1-2